Galactic Dark Matter Density: Addressing the Core-Cusp Problem - Shapiro, Jared Reese (Tufts Archival Research Center, 2023)
This undergraduate senior thesis analyzes light dark matter as a means of studying potential solutions to the core-cusp problem. We emphasize analysis of multiple scalar fields and focus on the relationship between density and radius, finding that it is quite difficult to fit the observed relation seen in galaxies.; Thesis (B.S.)--Tufts University, 2023.; Submitted to the Dept. of Physics and Astronomy.; Advisor: Mark Hertzberg.; Committee: Mark Hertzberg, Ken Olum, Fabio van Dissel.